Evaluation of Cosmetic Outcome Following Hypospadias Surgery Using the Hypospadias Objective Penile Evaluation (HOPE) Score (Journal of Paediatric Surgeons of Bangladesh, 2026)
Methods: This prospective observational study was conducted in the Department of Pediatric Surgery, Bangladesh Medical University (BMU), from July 2019 to June 2020. Seventy patients aged 1–14 years with anterior or mid-penile hypospadias who underwent surgical repair were included. Cosmetic outcomes were assessed preoperatively and postoperatively at 1, 3, and 6 months using the HOPE score. Statistical analysis was performed using SPSS version 26.0. Results: The mean total HOPE score increased significantly from 37.50 ± 9.05 preoperatively to 48.67 ± 3.41 at six months postoperatively. Significant improvement was observed in all evaluated domains, including meatal position, meatal shape, glans shape, penile skin, and penile axis. The cosmetic outcome remained stable from one month through six months postoperatively. Conclusion: The HOPE score is a reliable and objective tool for assessing cosmetic outcomes after hypospadias repair. Significant postoperative improvement in HOPE scores reflects successful surgical correction and satisfactory cosmetic results.Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 3-7